Length of Hatching, Hatching Weight and Sex Ratio in Domestic Chickens Crossed with Three Types of Roosters - Soleman Nggauhar Oktavianus (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The aim of the study was to determine hatching time, hatch weight, and sex ratio of domestic chickens crossed with various good males. The research was conducted in Mbatakapidu Village, Kota Waingapu District, East Sumba Regency for two months. This study used 30 native chickens aged 10 months in addition to three bangkok, ciliper or plucker, and pakhoy chickens. Parameters observed included: hatch time, hatch weight, and sex ratio. Data were analyzed using the ANOVA test. The results showed: 1) the average hatching time of native chickens crossed with three roosters: Pakhoy took 18.87 days, Ciliper took 18.53 days, and Bangkok took 18.53 days. 2) hatching weight of three roosters crossed with native chickens was 34.23 g for Bangkok, 33.18 g for Ciliper, and 31.72 g for Pakhoy. (3) The average sex ratio of DOC native chickens crossed with three roosters is Bangkok: male DOC is 20.41 percent, while female DOC is 44.90 percent. Caliper or Plucker: 14.29% male DOC, 33.67% female DOC, and Pakhoy: 7.00% male DOC and 27.55% female. The effect on the three observed parameters was determined by crossing native chickens with three roosters. Sex ratio had no effect on determining the sex of DOCs resulting from crossing native chickens with three roosters, however the use of three roosters had an effect on hatching time and weight. The sex ratio shows a very weak correlation with hatching time and hatching weight. To increase the productivity of free-range chickens it is important to cross them with several roosters.